Endophytic fungus Cladosporium tenuissimum DF11, an efficient inducer of tanshinone biosynthesis in Salvia miltiorrhiza roots. (February 2022) - Chen, Haimin; Chen, Jialing; Qi, Yao; Chu, Siyuan; Ma, Yao; Xu, Linna; Lv, Shiyi; Zhang, Haihua; Yang, Dongfeng; Zhu, Yonghong; Mans, Dennis RA.; Liang, Zongsuo
Abstract: Salvia miltiorrhiza is a traditional medicinal plant mainly used for cardiovascular and cerebrovascular disease treatment. Tanshinones are the main bioactive constituents of S. miltiorrhiza, which mainly accumulate around its root periderm tissue. Endophytic fungi are important bioelicitors or probiotics that can promote the accumulation of secondary metabolites and sustainable cultivation of medicinal plants. Among them, endophytic Cladosporium spp., possessing a variety of biotransformation and metabolic abilities, is an ideal elicitor source. Here, we used a gnotobiotic system to investigate the effects of the endophytic fungus Cladosporium tenuissimum DF11 on tanshinone biosynthesis in S. miltiorrhiza roots. The results showed that C. tenuissimum DF11 mainly colonizes the intercellular space of the root tissues and promotes tanshinone biosynthesis and accumulation in S. miltiorrhiza roots by upregulating the expression of the genes encoding for key enzymes HMGR, DXS, DXR, GGPPS, CPS, KSL and CYP76AH1 of the tanshinone biosynthesis pathway. The expression levels of almost all genes encoding for key enzymes reached the response peak in the first or second week after DF11 colonization. Taken together, the endophytic fungus C. tenuissimum DF11 could promote secondary metabolite accumulation in S. miltiorrhiza roots. These results indicate that DF11 will be a potential biofertilizer fungus to regulate and stabilize the quality of cultivated S. miltiorrhiza medicinal materials. Graphical abstract: Image 1 Highlights: Cladosporium tenuissimum DF11 promote the biosynthesis and accumulation of tanshinone in Salvia miltiorrhiza roots. C. tenuissimum DF11 can colonize into the intercellular space of the root tissues. C. tenuissimum DF11 upregulate the expression of genes encoding for key enzymes of tanshinone biosynthesis pathway. C. tenuissimum DF11 is a potential biofertilizer fungus for cultivated S. miltiorrhiza medicinal materials.